2007
DOI: 10.1073/pnas.0702080104
|View full text |Cite
|
Sign up to set email alerts
|

Transposition of the rice miniature inverted repeat transposable element mPing in Arabidopsis thaliana

Abstract: An active miniature inverted repeat transposable element (MITE), mPing, was discovered by computer-assisted analysis of rice genome sequence. The mPing element is mobile in rice cell culture and in a few rice strains where it has been amplified to >1,000 copies during recent domestication. However, determination of the transposase source and characterization of the mechanism of transposition have been hampered by the high copy number of mPing and the presence of several candidate autonomous elements in the ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
135
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(146 citation statements)
references
References 29 publications
(37 reference statements)
2
135
0
Order By: Relevance
“…2B). This finding is consistent with excision of mPing in Arabidopsis, where the vast majority of excision sites were found to contain only the TTA target site (11).…”
Section: The Resurrected Harbinger3 Dr Transposon Is Active In Human supporting
confidence: 79%
See 2 more Smart Citations
“…2B). This finding is consistent with excision of mPing in Arabidopsis, where the vast majority of excision sites were found to contain only the TTA target site (11).…”
Section: The Resurrected Harbinger3 Dr Transposon Is Active In Human supporting
confidence: 79%
“…Based on the presence of a SANT/Myb/trihelix domain (Fig. 1C) (4, 7), the Myb-like protein has been proposed to bind to the transposon DNA, where it either acts as a transcription factor of the transposase gene (9) and/or serves as a platform for transposase binding (11). Indeed, in contrast to the transposase, the Myb-like protein binds to six sites within the Harbinger3N DR transposon through its N-terminal trihelix domain (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarity searches based on TIR sequences have allowed the identification of autonomous class II elements, potentially responsible for the mobilization of MITEs (Feschotte and Mouches 2000;Feschotte et al 2003;Jiang et al 2003;Kikuchi et al 2003;Macas et al 2005;Saito et al 2005;Quesneville et al 2006). However, only a few recent studies have demonstrated, either by in vitro biochemical approaches (Loot et al 2006;Feschotte et al 2005) or in vivo (Yang et al 2007;Dufresne et al 2007), that class II transposases do have the potential to mobilize MITEs.…”
Section: Introductionmentioning
confidence: 99%
“…1 glume phenotype to wild type (Nakazaki et al 2003). The identification of an active element made it possible to discover that the transposable elements Ping and Pong supplied the transposase acting on mPing (Yang et al 2007). Movement of Stowaway MITEs in rice was also reported recently.…”
mentioning
confidence: 98%